PENERAPAN METODE DRILL TERHADAP HASIL BELAJAR DASAR AKUNTANSI KELAS X DI SMK PANCA BHAKTI SUNGAI RAYA - yarso, Jubairiyani; Ulfah, Maria; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe drill method is a practice with repeated practice to gain practical skills and dexterity about the knowledge learned. This study aims to determine the application of the drill method to the basic learning outcomes of class X accounting at SMK Panca Bhakti Sungai Raya. The research method used was an experimental study in the form of a pre-experimental research design with one group pretest posttest design. The data source of this study was 38 students in grade X accounting and the data was a sheet of grades from basic accounting learning outcomes with general journal learning materials. The results of this study indicate that without using the drill method student learning outcomes that achieve KKM only 26%. But after using the drill method student learning outcomes that reach the KKM to 47%. Thus an increase in KKM after applying the drill method. The results of subsequent studies indicate that, there are differences in student learning outcomes after the application of the drill method. This is evident from the significance value of 0.0000 <difficulty level 0.05.Keywords: Drill Method, Learning Outcomes